The problem of future professionals’ family relations - Боченко, О. В.; Гвоздюк, Я. В.; Котелевець, М. А. (Scientific notes of the pedagogical department, 2018)
The article is devoted to the analysis of institution of higher education students’ views on family relations creation in the modern world. The content of the article covers the problems of a new modern family and makes an attempt to give pedagogical help in preparation of students for family life. The article is of special interest because it has been written in collaboration with the students of Kharkiv National University named after V.Karazin, who find it necessary to study the issue of formation by an institution of higher education not only a highly qualified specialist but also a happy and successful personality who feels comfortable both at work but and in a family. One of the tasks of institutions of higher education is preparing of the young people for happy family life as well as for independent active working life. To prepare the students – future institutions of higher education graduates for family life it is important to examine and realize the understanding of family by young people, their view on how it should be built and what family happiness depends on, what kind of family is of a particular interest for modern young people. A modern family sets a number of difficult questions before young people. For example, a question about durability of love, marital compatibility, the ratio of material and spiritual values etc. In search of answers to the mentioned questions the everyday consciousness of the young turns to the experience of the older generations although this experience despite all its value doesn’t always meet the new demands of the modern life. This is why scientific awareness of the process of family development and its tendencies are so important. Having examined the questionnaires of the students of Kharkiv National University named after V.Karazin we came to the conclusion that despite the development of the modern society it is considered that the basis of a happy and strong family is love and mutual understanding and that introduction of specialized optional subjects concerning harmonization of family relations, creation of psychological-pedagogical service (a club, an organization etc.) for helping and supporting young students families in higher educational establishments are necessary.